Guarding the Faith of the Ummah: Religio-Intellectual Journey of Mohammad Rasjidi - Azra, Azyumardi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
Professor Mohammad Rasjidi, no doubt, is one of the Muslim intellectuals and national leaders of Indonesia's most prominent. He is the first Indonesian to obtain a bachelor's degree in philosophy from Cairo University and a Doctorate in Javanese spiritualism from the Sorbonne University, France. No less important, is the Minister of Religious Rasjidi first in the history of independent Indonesia, just as the existence of the Ministry of Religious questioned many circles.DOI: 10.15408/sdi.v1i2.859